2012
DOI: 10.1210/jc.2011-2759
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sleep Deprivation Enhances the Brain's Response to Hedonic Food Stimuli: An fMRI Study

Abstract: These results provide evidence that acute sleep loss enhances hedonic stimulus processing in the brain underlying the drive to consume food, independent of plasma glucose levels. These findings highlight a potentially important mechanism contributing to the growing levels of obesity in Western society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
151
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(167 citation statements)
references
References 15 publications
9
151
1
6
Order By: Relevance
“…Nedeltcheva et al 22 suggested that hypothalamic orexigenic neurons involved in the modulation of reward and motivation may be altered by restricting sleep duration. This is supported by data from St-Onge et al 43 and Benedict et al, 44 who found increased neuronal activation in the frontal cortex-involved in the reward value of food-in response to food stimuli after restricted sleep. It is possible that restricting sleep increases the reward-ing value of food while increasing endocrine drivers of food intake, such as ghrelin, leading to increased food consumption.…”
Section: Discussionsupporting
confidence: 52%
“…Nedeltcheva et al 22 suggested that hypothalamic orexigenic neurons involved in the modulation of reward and motivation may be altered by restricting sleep duration. This is supported by data from St-Onge et al 43 and Benedict et al, 44 who found increased neuronal activation in the frontal cortex-involved in the reward value of food-in response to food stimuli after restricted sleep. It is possible that restricting sleep increases the reward-ing value of food while increasing endocrine drivers of food intake, such as ghrelin, leading to increased food consumption.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, because our participant sample were young individuals without experience of night shift work, further work should establish whether these findings remain for individuals who are more representative of shift worker populations. It has been proposed that readily available unhealthy foods such as fast food in vending machines promotes poor nutritional habits amongst shift workers (28). Whilst some field studies of shift workers diets do suggest that their dietary patterns are altered, the studies are few and the findings are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Field-based studies have reported that shift workers consume more calories (26) and more saturated fats (27), often due to workers opting for snack options that are convenient and easy to obtain (28). However, studies evaluating the impact of shift work or shortened sleep on food preference have utilized self-reporting techniques, such as food diaries, questionnaires or interviews [eg, (5)].…”
mentioning
confidence: 99%
See 2 more Smart Citations